Tax Knowledge and Appropriate Tax Technology on Tax Compliance: Study on Micro Small and Medium Entreprises (MSMEs) in Batam City - Hidayati, Berlina; Utami , Indah Setia; Hermanto, Febrika Yogie (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research aims to reveal the attitude of Tax Compliance in Micro, Small, and Medium Enterprises (MSMEs) in Batam, with the independent variables of tax knowledge and tax technology, in line with the current development of technology-based industries. This research is quantitative research using an open questionnaire of 128 respondents from MSMEs in Batam. This research uses regression analysis with the SPSS application tool. This study shows that partially or simultaneously tax education, online tax registration, online tax reporting, and online tax remittances influence the tax compliance of MSMEs in Batam. Partially, this research reveals that mastery of tax knowledge can increase tax compliance among MSMEs in Batam, where the potential for increasing tax compliance is 65.3%. Besides, the appropriate tax technology that has the most influence on compliance is online tax reporting 78.8%; online tax remittance 75.6%; and online tax registration 70.8% in order of influence on tax compliance from largest to smallest. Then, simultaneous tax education, online tax registration, online tax reporting, and online tax remittances can increase MSME tax compliance in Batam by 68.6%. These findings confirm that there is potential to increase regional income through taxes in Batam by providing special treatment regarding tax education and appropriate tax technology variables to MSMEs.